Prevalence and molecular subtyping of Blastocystis in patients with Clostridium difficile infection, Singapore - Lei Deng; Huiyi Tay; Guangneng Peng; Jonathan W. J. Lee; Kevin S. W. Tan (Parasites & Vectors, 2021)
Abstract Background Blastocystis is a common anaerobic colonic protist in humans with controversial pathogenicity. Clostridium difficile (C. difficile) is the commonest cause of infectious diarrhea in healthcare settings. The prevalence and subtype (ST) characteristics of Blastocystis in patients with C. difficile infection (CDI) are rarely documented. Therefore, the present study was conducted to investigate the prevalence and subtype characteristics of Blastocystis in patients with suspicion of CDI in Singapore. Methods Fecal samples were collected from 248 patients presenting with suspected CDI from a single tertiary hospital in Singapore. C. difficile was diagnosed through positive glutamate dehydrogenase (GDH) with or without toxin A/B using enzyme immunoassay methods. The prevalence and subtype genetic characteristics of Blastocystis were determined by polymerase chain reaction (PCR) amplification and analysis of the barcode region of the SSU rRNA gene. Results The proportion of C. difficile in patients with healthcare-associated diarrhea in this study was 44% (109/248). Among the 109 C. difficile-positive patients, 59 (54.1%, 59/109) tested positive for toxigenic C. difficile, which was considered CDI. Based on the sequence analyses of the barcode region of the SSU rRNA gene, 10.1% (25/248) of the patients were found to be Blastocystis-positive, and three subtypes were identified: ST7 (64%, 16/25), ST1 (20%, 5/25), and ST3 (16%, 4/25). Remarkably, we found five patients with Blastocystis and C. difficile coinfection, and further subtype analysis showed two with ST7, two with ST1, and one with ST3. Conclusions To the best of our knowledge, this is the first study to investigate the subtype distributions of Blastocystis in patients with CDI in Singapore. We found ST7 to be the predominant subtype in diarrheal patients. The pathogenicity of ST7 has been strongly suggested in previous in vitro and mouse model experiments, further confirming its potential pathogenicity to humans.